Elections in Baduy Land Harmonizing Democracy with Indigenous Wisdom - Furqon, Wahyul (Jurnal Hukum Replik, 2024)
The 2019 election was a strategic moment in Indonesian democracy, particularly with the implementation of simultaneous elections encompassing the selection of the President and Vice President, as well as members of the People's Representative Council, the Regional Representative Council, and the Regional People's Representative Council. In the context of human rights, elections serve as a means of fulfilling the political rights of all citizens, including indigenous communities such as the Baduy. However, the electoral process within this indigenous community faced challenges stemming from differences between national law and customary law. Several key obstacles in organizing elections in the Baduy community included the rejection of electronic Identity Card registration, restrictions on election socialization and campaigning, the determination of polling station locations based on customary spiritual guidance, the prohibition of electricity usage during the voting process, and limited education affecting the recruitment of polling station officers.  Efforts by electoral organizers, such as the General Election Commission, the Election Supervisory Agency, and the National Commission on Human Rights, to safeguard the political rights of indigenous communities were conducted through a deliberative approach with indigenous leaders. Several compromises were reached, including voter registration based on village records without requiring electronic Identity Card ownership, the distribution of polling stations across 12 locations to improve accessibility, and the use of emergency lighting for vote counting. Meanwhile, challenges in limited education affecting the recruitment of polling station officers recruitment were addressed through a hybrid system that included both Baduy Luar (Outer Baduy) community members and non-Baduy individuals to meet the required administrative and literacy standards. The implementation of the 2019 election in the Baduy indigenous community demonstrated that electoral law can be applied flexibly while still respecting indigenous values without disregarding the principles of inclusivity and non-discrimination. Through a dialogue-based and compromise-driven approach, the election was conducted smoothly, achieving a participation rate of 70%, an increase from the 2018 local election. This electoral model, which respects local wisdom, can serve as a reference for ensuring the political rights of other indigenous communities in Indonesia. Keywords: 2019 Election, Baduy indigenous community, electoral law, political rights, customary law, discrimination, political participation.